Determination of Weak Zone using Wenner Configuration in Jendral Sudirman Street Section Muara Bulian, Batang Hari: Penentuan Zona Lemah menggunakan Konfigurasi Wenner di Ruas Jalan Jendral Sudirman Muara Bulian, Batang Hari - Fitriyanti Retno Siwi; Linda Handayani; Buhaira Buhaira (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2026)
Jenderal Sudirman road is an alternative road used to avoid traffic congestion located on the National Causeway in Muara Bulian District, Batang Hari, Jambi. The road has a weak zone so that the purpose of this study, determines the subsurface structure and distribution of the weak zone on Jenderal Sudirman roads, Muara Bulian, Batang Hari, Jambi. The weak zone, namely the soil, decreases due to a large load so that there is ablaze on the road. Road damage one of which is damaged edges can result in accidents. Determination of weak zones using Wenner Configuration Geoelectric Method and DCPT data. Lines 1 and 2 are in the alluvial area (Qa) and Line 3 and 4 in the Kasai Formation (QTk). The first line of the weak zone at 17 – 44 m with a thickness of 3 – 10 m is located near the surface and below the surface at 45 – 95 m is estimated at a depth of 3 – 10 m with a thickness of 8 m with fine sandstone lithology. The weak zone on line 2 is near the surface at 20 – 28 m is estimated to be 6 m thick and at 40 – 77 m it is estimated at a depth of 3 – 5 m with a thickness of 2 – 6 m located under the surface of the clay periphery to a layer of fine sand saturated with water. The weak zone on line 3 is located at 20 – 56 m with a depth of 8 m and a thickness of 6 m located below the surface. The weak zone on track 4 is located at 35 – 87.5 m with a depth of 3 m and a thickness of 3 – 10 m. DCPT results from Robertson's 1986 chart and sondir graph obtained a weak zone at a depth of 0 m to 10.60 m with a conus pressure below 20 kPa.